2012
DOI: 10.1051/0004-6361/201118428
|View full text |Cite
|
Sign up to set email alerts
|

P/2010 a2 Linear

Abstract: P/2010 A2 is an object on an asteroidal orbit that was observed to have an extended tail or debris trail in January 2010. In this work, we fit the outburst of P/2010 A2 with a conical burst model, and verify previous suspicions that this was a one-time collisional event rather than a sustained cometary outburst, implying that P/2010 A2 is not a new main belt comet driven by ice sublimation. We find that the best-fit cone opening angle is ∼40• to ∼50• , in agreement with numerical and laboratory simulations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
7
15
0
Order By: Relevance
“…Because the P/2010 A2 dust particles have a composition that is similar to ordinary chondrites (Kim et al 2012), we assumed ρ d = 3000 kg m −3 , which is a typical value for their bulk density (Britt et al 2002). This assumption is consistent with previous research (Jewitt et al 2010Kleyna et al 2013). K = 5.7 × 10 −4 kg m −2 is a constant, and Q pr is a radiation pressure coefficient that we considered to be unity (Burns et al 1979).…”
Section: Model Descriptionsupporting
confidence: 91%
See 2 more Smart Citations
“…Because the P/2010 A2 dust particles have a composition that is similar to ordinary chondrites (Kim et al 2012), we assumed ρ d = 3000 kg m −3 , which is a typical value for their bulk density (Britt et al 2002). This assumption is consistent with previous research (Jewitt et al 2010Kleyna et al 2013). K = 5.7 × 10 −4 kg m −2 is a constant, and Q pr is a radiation pressure coefficient that we considered to be unity (Burns et al 1979).…”
Section: Model Descriptionsupporting
confidence: 91%
“…There are several ideas for the creation of the arc-like features. For example, assuming little or no radiation pressure, it would be possible to replicate arc features that are consistent with the images at a single epoch or for a certain short time duration Kleyna et al 2013). However, as we mentioned above, these models do not reproduce the morphology and brightness distribution at different epochs.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of P/2012 F5 (Stevenson et al 2012;Moreno et al 2012), 596 (Hsieh et al 2012a;Ishiguro et al 2011a,b;Jewitt et al 2011;Moreno et al 2012), and P/2010 A2 (Jewitt et al 2010;Snodgrass et al 2010;Jewitt et al 2011;Hainaut et al 2012b;Kim et al 2012;Kleyna et al 2013) has been interpreted as the effect of impacts by small asteroids.…”
Section: Introductionmentioning
confidence: 99%
“…The disrupted P/2010 A2 went unobserved from this initial event to (pre-discovery) observations taken in 2009 November 22 (Jewitt et al 2011a). The basic features and possible interpretation of P/2010 A2 have been confirmed by a number of independent investigators (Paper 1; Snodgrass et al 2010;Hainaut et al 2012;Kim et al 2012;Kleyna et al 2013). In particular, Kleyna et al (2013) have presented a detailed impact model that purports to fit many of the observed properties of the tail structure.…”
Section: Introductionmentioning
confidence: 77%